AB0299 The Reasons for Withdrawal of Biological Dmards According To The Russian Registry of Patients with Rheumatoid Arthritis. (15th July 2016) - Satybaldyev, A.; Karateev, D.; Nassonov, E.; Luchikhina, E.; Lukina, G.; Nikolenko, M.; Bilinskaya, M.; Dmitrieva, M.; Bogoderova, L.; Lapkina, N.; Chichasova, N.; Sorotskaya, V.; et al.
Abstract : Background: Russian register of patients with inflammatory arthritis started in 2012 as a register of RA ("All-Russian register of Rheumatoid Artritis"- ARRA) now transformed into "Observational REgister of arthritis in cLinical practice" (OREL), including patients with rheumatoid arthritis (RA), psoriatic arthritis and adults with juvenile arthritis. (RA), psoriatic arthritis and adults with juvenile arthritis. Objectives: To study reasons for withdrawal of biological DMARDs in patients with RA in clinical practice in Russia. Methods: Data of 1398 pts with RA (286 men, 1112 women, medium age of 50, 5 years), treated of biological DMARDs, were included in OREL registry from 01 Mar 2012 to 30 Mar 2015. Results: 320 pts (22.8%) had withdrawals of biologics during this period. In 77 pts (23.4%) the reason for withdrawal was primary lack of efficacy or secondary loss of response; in 54 pts (16.9%) - adverse events (AE) or serious adverse events (SAE). In 80 pts (25.0%) biologic therapy has been stopped due to continuous remission; 109 pts (32.5%) had administrative reasons (lack of funding etc.). Conclusions: Frequencies of withdrawals due to lack of efficacy or loss of response among biological DMARDs were comparable. Etanercept has been withdrawn due to long term remission more often than other biologics. Lack of funding is still an important cause of withdrawal of biological therapy of RA. Disclosure of Interest: None declared